PERAN BUDAYA BELALEK MENANAMKAN CIVIC COMMITMENT MASYARAKAT DESA SUNGAI DUNGUN KECAMATAN SUNGAI KUNYIT - Alfiani, Alma; Aminuyati, Aminuyati; Atmaja, Thomy Sastra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to determine the role of belalek culture in instilling civic commitment in the people of Sungai Dungun Village, Sungai Kunyit District, Mempawah Regency. The research method uses a qualitative approach with a descriptive research type. Sources of data in this study were observations of the preparation and implementation of belalek culture, interviews with the Head of Sungai Dungun Village and the head of the RT and the community in Sungai Dungun Village, photo documentation of the implementation of belalek culture and photos during research. Data collection tools in the form of observation guidelines, interview guidelines and documentation. The results of the study show that preparation before the implementation of belalek culture is inviting the community to participate in belalek, preparing tools, materials and consumption. The implementation of the belalek culture in Sungai Dungun Village is carried out by working together alternately depending on who will be the host. The form of belalek culture instills civic commitment, namely through community cooperation. Obstacles to implementing belalek culture are the diminishing public interest in taking part in belalek, people who are busy with their respective jobs, the weather is not supportive and there is one member of the community who is sick during the implementation of belalek. The solution to overcoming obstacles is paying wages in the form of money to attract the public's interest, implementing a belalek culture on working holidays, the community holds deliberations for the implementation of belek, people who are sick are told to rest.